Penjernihan Air Payau Sungai Serdang dengan Limbah Sekam Padi Sebagai Bahan Dasar Zeolit dalam Menurunkan Kadar Logam Besi (Fe) Dan Mangan (Mn) di Kabupaten Tanjung Jabung Barat - Abul Ainin Hapis; Mukhlis Sanuddin (Universitas Batanghari Jambi, 2021)
Rice husk ash is a waste from burning rice husks which causes pollutants that can pollute the environment so it is necessary to use it to increase its economic value and reduce its negative impact on the environment, one of which is used as a basic material for making zeolite. This study aims to utilize rice husk ash waste as a basis for making zeolite which is used as an adsorbent to purify and reduce metal content in brackish water. This study is an experimental study. Where, this research was conducted using water samples in the Serdang Jaya area, Tanjung Jabung Barat Regency, Jambi. 10 liters of water samples were taken by a purification process using two purification methods, then the water filtering process was left for 30-60 minutes until the water looked clear. After the water is clear, the iron (Fe) and manganese (Mn) levels are tested using atomic absorption spectrophotometry to see the decrease in metal levels in the water. Water purification is carried out using a procedure consisting of water, coral, activated charcoal, zeolite, sand and palm fiber. The results of FTIR analysis showed that the Al and Si functional groups were formed from zeolite of rice husk. The XRD analysis results showed the formation of compound structures, namely Aluminum Oxide and Sodium Silica. The results of AAS analysis of water purification showed a more effective decrease in turbidity levels and a decrease in iron (Fe) levels by 0.1672 mg / l and manganese (Mn) metal by <0.01 mg / l. Zeolites made from rice husk ash are zeolite A (Na2O.Al2O3.2SiO2.4,5H2O) and Zeolites from rice husk ash can be used in the purification process to reduce levels of Fe metal 96.71% and metal content of manganese (Mn) amound 98 , 23%.